High-intensity interval training in team sports: Testing, monitoring and prescription - Scott, T. J. U. (Victoria University, 2017)
Aerobic fitness and repeated high-intensity efforts have been shown to be a determinant in the performance of team sports, especially in the ability to finish a match, to cover a distance, to repeat and recover between sprints and explosive movements (e.g. accelerations, changes of direction; COD) and to reduce the deterioration in some technical skill. Due to this, coaches must appropriately develop these capacities to adequately prepare athletes for match-play demands. High-intensity interval training is considered an effective and time efficient means to optimise individual physiological adaptation. However, the best processes which examine these qualities (physical testing protocols), prescribe training and monitor the response of this training requires attention, particularly in team sport athletes that possess heterogenous physical attributes. Therefore, this thesis aimed to examine a valid and reliable approach to assess the training outcome as well as prescribe and monitor the training process in rugby league athletes.